Charge transport mechanism of self-powered GaN p-i-n α-particle detector. (July 2020) - Geng, Xinlei; Xia, Xiaochuan; Liu, Jun; Cui, Xingzhu; Sun, Zhonghao; Huang, Huishi; Xue, Dongyang; Liang, Xiaohua; Meng, Xiangcheng; Liang, Hongwei
Abstract: In this paper, a model based on charge collection efficiency ( CCE ) has been developed to investigate the charge transport mechanism of self-powered GaN p-i-n α-particle detector. To validate the model, a GaN p-i-n α-particle detector with 20 μm unintentionally doped layer was fabricated and irradiated by 5.48 MeV α particles. The contribution of hole diffusion to CCE was observed to be 17% at zero bias and slightly decreased to 14% at a reverse voltage of 10 V. The consistency between the experimental result and theoretical calculation demonstrates that charge transport mechanism is dominated by hole diffusion of non-depleted region. This work proves the appreciable advantage of GaN p-i-n detectors to detect α particles even without external power supply. Highlights: A self-powered GaN p-i-n α-particle detector has been successfully prepared. The thickness of unintentionally doped GaN layer can reach 20 μm. Charge transport mechanism of the detector has been investigated.